Thermal stability and reduction of iron oxide nanowires at moderate temperatures - Paolone, Annalisa; Angelucci, Marco; Panero, Stefania; Betti, Maria Grazia; Mariani, Carlo (Beilstein Journal of Nanotechnology, 2014)
Background: The thermal stability of iron oxide nanowires, which were obtained with a hard template method and are promising elements of Li-ion based batteries, has been investigated by means of thermogravimetry, infrared and photoemission spectroscopy measurements.Results: The chemical state of the nanowires is typical of the Fe2O3 phase and the stoichiometry changes towards a Fe3O4 phase by annealing above 440 K. The shape and morphology of the nanowires is not modified by moderate thermal treatment, as imaged by scanning electron microscopy.Conclusion: This complementary spectroscopy–microscopy study allows to assess the temperature limits of these Fe2O3 nanowires during operation, malfunctioning or abuse in advanced Li-ion based batteries.
Keywords: IR spectroscopy; iron oxide; nanowires; scanning electron microscopy (SEM); thermogravimetry; XPS

(untitled) - Tarascon, J.-M.; Armand, M. (Nature, 2001)

(untitled) - Poizot, P.; Laruelle, S.; Grugeon, S.; Dupont, L.; Tarascon, J.-M. (Nature, 2000)

(untitled) - Taberna, P. L.; Mitra, S.; Poizot, P.; Simon, P.; Tarascon, J.-M. (Nat. Mater., 2006)

(untitled) - Wu, H. B.; Chen, J. S.; Hng, H. H.; Lou, X. W. D. (Nanoscale, 2012)

(untitled) - Larcher, D.; Masquelier, C.; Bonnin, D.; Chabre, Y.; Masson, V.; Leriche, J.-B.; Tarascon, J.-M. (J. Electrochem. Soc., 2003)

(untitled) - Chen, Y. X.; He, L. H.; Shang, P. J.; Tang, Q. L.; Liu, Z. Q.; Liu, H. B.; Zhou, L. P. (J. Mater. Sci. Technol., 2011)

(untitled) - Chou, S.-L.; Wang, J.-Z.; Chen, Z.-X.; Liu, H.-K.; Dou, S.-X. (Nanotechnology, 2011)

(untitled) - Wang, Z.; Luan, D.; Madhavi, S.; Li, C. M.; Lou, X. W. D. (Chem. Commun., 2011)

(untitled) - Wang, Z.; Zhou, L.; Lou, X. W. D. (Adv. Mater., 2012)

(untitled) - Zhang, Q.; Shi, Z.; Deng, Y.; Zheng, J.; Liu, G.; Chen, G. (J. Power Sources, 2012)

(untitled) - Koo, B.; Xiong, H.; Slater, M. D.; Prakapenka, V. B.; Balasubramanian, M.; Podsiadlo, P.; Johnson, C. S.; Rajh, T.; Shevchenko, E. V. (Nano Lett., 2012)

(untitled) - Ding, Y.; Li, J.; Zhao, Y.; Guan, L. (Mater. Lett., 2012)

(untitled) - Zhang, J.; Huang, T.; Liu, Z.; Yu, A. (Electrochem. Commun., 2013)

(untitled) - Zou, Y.; Wang, Y. (ACS Nano, 2011)

(untitled) - Li, X.; Lei, Y.; Li, X.; Song, S.; Wang, C.; Zhang, H. (Solid State Sci., 2011)

(untitled) - Chen, D.; Ji, G.; Ma, Y.; Lee, J. Y.; Lu, J. (ACS Appl. Mater. Interfaces, 2011)

(untitled) - Qu, Q.; Yang, S.; Feng, X. (Adv. Mater., 2011)

(untitled) - Hsieh, C.-T.; Lin, J.-Y.; Mo, C.-Y. (Electrochim. Acta, 2011)

(untitled) - Lee, S.-H.; Sridhar, V.; Jung, J.-H.; Karthikeyan, K.; Lee, Y.-S.; Mukherjee, R.; Koratkar, N.; Oh, I.-K. (ACS Nano, 2013)

(untitled) - Guo, S.; Zhang, G.; Guo, Y.; Yu, J. C. (Carbon, 2013)

(untitled) - Wang, G.; Wang, H.; Cai, S.; Bai, J.; Ren, Z.; Bai, J. (J. Power Sources, 2013)

(untitled) - Jin, B.; Liu, A.-H.; Liu, G.-Y.; Yang, Z.-Z.; Zhong, X.-B.; Ma, X.-Z.; Yang, M.; Wang, H.-Y. (Electrochim. Acta, 2013)

(untitled) - Prakash, R.; Fanselau, K.; Ren, S.; Mandal, T. K.; Kübel, C.; Hahn, H.; Fichtner, M. (Beilstein J. Nanotechnol., 2013)

(untitled) - Zhao, H.; Pan, L.; Xing, S.; Luo, J.; Xu, J. (J. Power Sources, 2013)

(untitled) - Hong, I.; Angelucci, M.; Verrelli, R.; Betti, M. G.; Panero, S.; Croce, F.; Mariani, C.; Scrosati, B.; Hassoun, J. (J. Power Sources, 2014)

(untitled) - Reddy, M. V.; Yu, T.; Sow, C. H.; Shen, Z. X.; Lim, C. T.; Subba Rao, G. V.; Chowdari, B. V. R. (Adv. Funct. Mater., 2007)

The Iron Oxides - Cornell, R. M.; Schwertmann, U. (Wiley-VCH, 2003)

(untitled) - Chambers, S. A.; Thevuthasan, S.; Joyce, S. A. (Surf. Sci., 2000)

(untitled) - Yamashita, T.; Hayes, P. (Appl. Surf. Sci., 2008)

(untitled) - Yang, D.-Q.; Sacher, E. (J. Phys. Chem. C, 2009)

(untitled) - Mills, P.; Sullivan, J. L. (J. Phys. D: Appl. Phys., 1983)

(untitled) - Zimmermann, R.; Steiner, P.; Claessen, R.; Reinert, F.; Hüfner, S.; Blaha, P.; Dufek, P. (J. Phys.: Condens. Matter, 1999)